Vegetarianism and weight status: What are the differences in eating styles, impulsivity, and emotional competences? A preliminary study. Issue 4 (July 2022) - Hanras, Eva; Boujut, Emilie; Ruffault, Alexis; Messager, Diane; Rives-Lange, Claire; Barsamian, Charles; Carette, Claire; Lucas-Martini, Léa; Czernichow, Sébastien; Dorard, Géraldine
Abstract: Recent studies suggest that vegetarian diets may be recommended to promote weight loss in individuals living with obesity. However, limited studies have examined psychological factors (e.g., eating styles, impulsivity) among individuals who have adopted this type of diet, even though these factors are known to play a role in being overweight. The primary objective of the present study was to compare these characteristics in participants living with obesity or those with normal-weight across diet types. Participants were recruited from two hospital nutrition departments and the general population. They completed a diagnostic interview assessing the presence of an eating disorder, followed by self-administered questionnaires measuring dysfunctional eating styles (DEBQ), impulsivity (UPPS), and emotional competence (PEC). Vegetarian participants living with obesity engaged in more dysfunctional eating styles than did normal-weight omnivores and experienced more emotional difficulties than did both normal-weight omnivores and vegetarians. In contrast, there were no significant differences between omnivore participants living with obesity and those in the other groups. Moreover, participants living with obesity had comparable emotion regulation abilities to normal-weight participants. These results suggest that emotion regulation deficits can more likely be explained by the presence of psychopathological traits than by being overweight or one's choice of diet. Highlights: Individuals living with obesity have comparable emotion regulation abilities to normal-weight individuals. Vegetarians living with obesity engage in more emotional eating than do normal-weight omnivore individuals. Vegetarians living with obesity experience more emotion regulation difficulties than do normal-weight individuals.